What did PISA and TIMSS ever do for us?: The potential of large scale datasets for understanding and improving educational practice - Elliott, Julian; Stankov, Lazar; Lee, Jihyun; Beckmann, Jens F (Comparative education, 2019)
There appears to be something of an intellectual and philosophical gulf between education researchers who seek insights from statistical analyses of complex data-sets such as those provided by the OECD (PISA), and others who seek to develop rich, contextualised socio-historical understandings that can shed light upon why particular classroom practices operate and are sustained within a given milieu. This paper outlines these different perspectives, with particular reference to non-cognitive factors. Detailed analysis of the roots of high academic achievement, and associated challenges to student wellbeing, in many East Asian countries, is provided. The important influence of broad political and societal factors is highlighted by reference to cross-cultural differences across a large number of countries. The paper concludes by stating that while data from large datasets can assist in gaining greater understanding of cross-cultural differences, to be meaningful, such analyses should be incorporated within complex ecosystemic accounts. (übernommen).